Deforestation-Free Peruvian Coffee: Challenges and Opportunities in the European Market (Journal of Business, Universidad del Pacífico (Lima, Peru), 2026)
The European Union’s new regulation – (UE) 2023/1115, which will allow only deforestation-free commodities to be imported starting in late 2025, will significantly impact the structure of the agri-food market, where Peru plays a role as an exporter of coffee, cocoa, and oil palm. This paper focuses on the case of coffee, analyzing the production in the current value chain dynamics and the European market's role in generating economic, social, and environmental benefits.Previously, coffee’s environmental attributes were voluntarily validated through organic or biodiversity-friendly certifications (e.g., Smithsonian Bird Friendly Coffee). However, the new regulation mandates compulsory validation as «deforestation-free coffee» (CLD). This shift presents both challenges and opportunities for Peru, requiring strong coordination between the public and private sectors.The study outlines key recommendations, including the promotion of ecosystem services and overcoming structural barriers to enable Peru’s coffee sector to adapt to this evolving market landscape.
Keywords: deforestation-free coffee; ecosystem services marketing